Development and Validation of a New Robust RP-HPLC Method for the Simultaneous Quantitation of Levonorgestrel and Ethinylestradiol in Bulk and Pharmaceutical Dosage Form - Kumar, V. Pavan (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2024)
The present study was mainly focused on developing and validating a new isocratic, simple, rapid, precise, accurate, and stable reverse phase high-performance liquid chromatography method for a combination of levonorgestrel and ethinylestradiol. The separation was achieved on a C18 µ-bondopak column (250 mm*4.6 mm) using a mobile phase consisting of buffer, water, and acetonitrile in the ratio of 40:20:40 (buffer-0.1% v/v triethylamine pH-3.0 followed by 0.9 mL/min flow rate. The wavelength detection was at 260 nm. The chromatographic retentions were stable at 3.604 min for levonorgestrel and 5.142 min for ethinylestradiol. Linearity concentrations were established in the range of 20–100 µg/mL for levonorgestrel and 10–50 µg/mL for ethinylestradiol and the correlation coefficient for the above drugs was 0.999. The relative standard deviation of inter-and intra-day precision was <2%. The proposed method provides a useful tool for the quantification of levonorgestrel and ethinylestradiol for their assay. This method is simple, accurate, and reproducible and can be successfully employed for routine quality control analysis of drugs in pure as well as in pharmaceutical dosage form. The main advantage of the developed method was its high specificity for the estimation of levonorgestrel and ethinylestradiol.